Peroxisome Proliferator-Activated Receptor-Gamma Reduces ER Stress and Inflammation via Targeting NGBR Expression - Ma, Jialing; Zeng, Peng; Liu, Lipei; Zhu, Mengmeng; Zheng, Juan; Wang, Chengyi; Zhao, Xiaokang; Hu, Wenquan; Yang, Xiaoxiao; Duan, Yajun; Han, Jihong; Miao, Qing R.; et al. (Frontiers in Pharmacology, 2022)
Previous studies have shown that increased Nogo-B receptor (NGBR) expression in the liver may improve insulin sensitivity by reducing endoplasmic reticulum stress (ER stress) and activating the AMPK pathway. In this study, we found that PPARγ ligands (rosiglitazone or pioglitazone) increased NGBR mRNA and protein expression in HepG2 cells, HUVECs, and mouse primary hepatocytes. Furthermore, promoter analysis defined two PPREs (PPARγ-responsive elements) in the region of the NGBR promoter, which was further confirmed by the ChIP assay. In vivo, using liver-specific PPARγ deficient mice, we identified the key role of PPARγ expression in pioglitazone-induced NGBR expression. Meanwhile, the basal level of ER stress and inflammation was slightly increased by NGBR knockdown. However, the inhibitory effect of rosiglitazone on inflammation was abolished while rosiglitazone-inhibited ER stress was weakened by NGBR knockdown. Taken together, the results of the present study show that NGBR is a previously unrecognized target of PPAR activation and plays an essential roles in PPARγ-reduced ER stress and inflammation.